WORKSHOP PENGENALAN TOOL DEEP LEARNING UNTUK KLASIFIKASI GAMBAR UNTUK MENENTUKAN STATUS SOSIAL DAN REKOMENDASI BANTUAN SOSIAL - Yusuf, Mohamad; Hakim, Lukman; Rushendra; Awang, Nungky (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
This Community Service Activity was carried out as an effort to improve operational efficiency in travel service business actors, especially PT Swabina Gatra Travel, through optimizing the use of the Bookswantastic and Jurnal ID digital systems. Although both systems have been implemented to support the ticket booking process and financial transaction recording, the lack of integration of these systems still causes obstacles such as data duplication, price input errors, and increased employee workload. Through this activity, the community service team provides education-based solutions and assistance in the form of training on the use of more effective digital systems, preparation of internal Standard Operating Procedures (SOPs), and socialization of the potential for system integration through API technology. It is hoped that this activity can improve the understanding and skills of business actors in managing digital-based business processes efficiently, while strengthening the readiness for digital transformation in the travel service sector.